Development of a Fluoride Riboswitch-based Whole-cell Biosensor for Detecting Fluoride in Drinking Water - Kaushalya, K.A.D.; Ariyaratne, W.M.R.; Silva, G.N. (University of Colombo, 2024)
Drinking water is the main dietary source of fluoride for humans. Despite the benefits, high ingestion of fluoride causes adverse health concerns. Interference with other ions is a major drawback associated with conventional methods available for detection of fluoride concentration in drinking water. Bacterial riboswitches are well known for their high selectivity towards the ligand. The novel method ...
Keywords: Riboswitch; Fluoride Ions; Drinking Water; Portable Biosensor; E. coli